Comparative genomics of the fish pathogens Edwardsiella ictaluri 93-146 and Edwardsiella piscicida C07-087. Issue 2 (14th February 2020) - Tekedar, Hasan C.; Blom, Jochen; Kalindamar, Safak; Nho, Seongwon; Karsi, Attila; Lawrence, Mark L.
Abstract : Edwardsiella ictaluri and Edwardsiella piscicida are important fish pathogens affecting cultured and wild fish worldwide. To investigate the genome-level differences and similarities between catfish-adapted strains in these two species, the complete E. ictaluri 93-146 and E. piscicida ﻿ C07-087 genomes were evaluated by applying comparative genomics analysis. All available complete (10) and non-complete (19) genomes from five Edwardsiella species were also included in a systematic analysis. Average nucleotide identity and core-genome phylogenetic tree analyses indicated that the five Edwardsiella species were separated from each other. Pan-/core-genome analyses for the 29 strains from the five species showed that genus Edwardsiella members have 9474 genes in their pan genome, while the core genome consists of 1421 genes. Orthology cluster analysis showed that E. ictaluri and E. piscicida ﻿ ﻿ genomes have the greatest number of shared clusters. However, E. ictaluri and E. piscicida ﻿ also have unique features; for example, the E. ictaluri genome encodes urease enzymes and cytochrome o ubiquinol oxidase subunits, whereas E. piscicida ﻿ genomes encode tetrathionate reductase operons, capsular polysaccharide synthesis enzymes and vibrioferrin-related genes. Additionally, we report for what is believed to be the first time that E. ictaluri 93-146 and three other E. ictaluri genomes encode a type IV secretion system (T4SS), whereas none of the E. piscicida ﻿ genomes encode this system. Additionally, the E. piscicida ﻿ C07-087 genome encodes two different type VI secretion systems. E. ictaluri genomes tend to encode more insertion elements, phage regions and genomic islands than E. piscicida ﻿. We speculate that the T4SS could contribute to the increased number of mobilome elements in E. ictaluri compared to E. piscicida ﻿. Two of the E. piscicida ﻿ genomes encode full CRISPR-Cas regions, whereas none of the E. ictaluri genomes encode Cas proteins. Overall, comparison of the E. ictaluri and E. piscicida ﻿ genomes reveals unique features and provides new insights on pathogenicity that may reflect the host adaptation of the two species.